Nuclear desalination joint symposium held at the Institute of Civil Engineers, 1-7 Great George Street, London SW1, on Monday, 30 October 1967, by the British Nuclear Energy Society and the British Nuclear Forum. (British Nuclear Energy Society, 1968)
This title contains the proceedings of a joint BNES/British Nuclear Forum held on 30 October 1967.